Я подарю тебе Луну: [повести] - Мавлютова Галия (Русский любовный роман, 2007)
Экземпляры: ф. 24 (20210325) / Инвентарный номер: 61196 / Цена: 10.00 / Авт.знак: М 12 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4